Application of Big Data Technology in Smart Field Forest Ecotourism - Li Qiong (Forest Chemicals Review)
In recent years, urban people begin to focus on the alpine jungle, which makes the wild jungle tourism develop rapidly. This paper summarizes the connotation of smart tourism and big data, and analyzes the influencing factors of Sipsongpanna smart tourism service platform construction. This paper briefly analyzes the feasibility, advantages, needs and other aspects of the platform construction, and puts forward the model framework of Sipsongpanna smart tourism service platform based on big data. The model builds six tourism application service platforms around three aspects of smart tourism management, marketing and service. The platform has built the application subsystem of thematic tourism big data with different functions, and each subsystem closely relies on big data to fulfill its own responsibilities. This makes big data really applied to smart tourism, and realizes the collection, storage, analysis and application of smart tourism data. The results of data analysis and processing can provide decision-making reference for the government, tourism enterprises, tourists and other stakeholders. Finally, the paper puts forward suggestions on the implementation path and Development Countermeasures of Sipsongpanna smart tourism service platform, aiming at promoting the comprehensive, coordinated and sustainable development of Sipsongpanna smart tourism.